Click chemistry-mediated tumor-targeting of SN38-loaded nanoparticles using trastuzumab - Yoo, Jihye; Choi, Sangkee; Son, Jihwan; Yi, Gawon; Kim, Eunha; Koo, Heebeom (Biochemical and Biophysical Research Communications, 2019)
For efficient drug delivery, we introduce a click-chemistry-mediated two-step tumor-targeting strategy for nanoparticles (NPs). We modified HER2-binding trastuzumab with trans-cyclooctene (TCO-Trb), and fabricated tetrazine-modified NPs containing the anticancer drug, SN38 (SN38-Tz-NPs). To target tumor cells with the Tz-NPs, the tumor cells are first treated with TCO-Trb. The TCO-Trb binds HER2s and presents multiple TCO groups on the cell surface. Subsequently, the cells are treated with SN38-Tz-NPs that can bind the cell surface via click chemistry between Tz and TCO. This click chemistry-mediated binding resulted in enhanced tumor-targeting of Tz-NPs to the target tumor cells. In our study, this strategy was performed and analyzed in vitro and in vivo, and the results show that this is a promising strategy for tumor-targeted drug delivery by NPs.
Keywords: Animals; Cell Line, Tumor; Click Chemistry; Cyclooctanes; Drug Delivery Systems; Irinotecan; Mice, Inbred BALB C; Mice, Nude; Nanoparticles; Neoplasms, Experimental; Protein Binding; Receptor, ErbB-2; Tissue Distribution; Topoisomerase I Inhibitors; Trastuzumab; Click chemistry; Drug delivery; In vivo imaging; Nanoparticle; SN38; Trastuzumab